1995
DOI: 10.1152/jn.1995.73.4.1653
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional differences distinguish principal from nonprincipal cells in the guinea pig MSO slice

Abstract: 1. Principal cells in the medial superior olive (MSO) receive low-frequency information from both ears via left and right cochlear nuclei. In vivo extracellular records suggest that some MSO neurons respond optimally only when the binaural acoustic signal has a precise interaural delay. Thus MSO cells, in particular principal cells, are thought to be the first stage in the processing of interaural time difference cues that provides information as to the location of a low-frequency sound in space. 2. Despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 0 publications
10
104
0
1
Order By: Relevance
“…Yet another possibility is that inhibition occurs at ITDs at which binaural coincidences do not, counteracting the dispersive effects of monaural coincidences. There is ample evidence that inhibitory inputs are present and functional (Adams and Mugnaini 1990;Banks and Smith 1992;Brand et al 2002;Cant and Hyson 1992;Covey et al 1991;Sanes 1993, 1994;Kiss and Majorossy 1983;Kuwabara and Zook 1992;Smith 1995;Spangler et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Yet another possibility is that inhibition occurs at ITDs at which binaural coincidences do not, counteracting the dispersive effects of monaural coincidences. There is ample evidence that inhibitory inputs are present and functional (Adams and Mugnaini 1990;Banks and Smith 1992;Brand et al 2002;Cant and Hyson 1992;Covey et al 1991;Sanes 1993, 1994;Kiss and Majorossy 1983;Kuwabara and Zook 1992;Smith 1995;Spangler et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Using a multicompartment model of avian NL, Agmon-Snir et al (1998) showed that the systematic dependence of dendritic length on tonotopic position observed in chick NL (Smith and Rubel 1979) is essential to obtain good ITD tuning over a wide range of frequencies. While our single compartment model cannot address the effects of cellular morphology on coincidence detection, there is no evidence for a tonotopic gradient in dendritic length or synaptic input strength in mammalian MSO (Henkel and Brunso-Bechtold 1990;Smith 1995). Using a gerbil MSO slice preparation, Mathews et al (2010) demonstrated that a gradient of G KLT along the dendrites of MSO neurons increased the modulation of rate-ITD curves.…”
Section: Relation To Other Models and Limitations Of The Modelmentioning
confidence: 91%
“…Similarly, single neurons in the inferior colliculus (IC) of acutely deafened cats can exhibit good ITD sensitivity to electric pulse trains at low pulse rates (G100 pps) for moderate stimulus levels, but their ITD sensitivity degrades at higher pulse rates where many neurons show only an onset response (Smith andDelgutte 2007, 2008;Hancock et al 2012). The narrow range of pulse rates yielding good ITD sensitivity with electric stimulation in deaf animals contrasts with the wider range of frequencies over which ITD sensitivity to pure tones is observed in normal hearing animals in both the medial superior olive (MSO) (Yin and Chan 1990) and the IC (Kuwada and Yin 1983;Kuwada et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Peaks in the PSTH indicate a 1-Hz modulation in the neuron's discharge pattern (3 complete response cycles over the 3-s stimulus presentation). The rate of the response modulation equates to the difference between the pure-tone frequency in one ear and the AM rate in the other, suggesting the possibility that it results from binaural integration of temporally phase-locked inputs, a process usually considered to arise in the medial superior olive of the brain stem, below the level of the IC, and that requires specialized cell types (Smith 1995;Smith et al 1998) and synaptic mechanisms (Agmon-Snir et al 1998; Forsythe and Barnes-Davies 1993) considered unique to the lower binaural brain stem. Figure 2 shows the responses of another IC neuron, with an audio-visually determined CF of 364 Hz, to low-frequency pure tones and high-frequency AM tones.…”
Section: R E S U L T Smentioning
confidence: 99%